FORMULASI DAN KARAKTERISASI MI BEBAS GLUTEN TINGGI PROTEIN BERBAHAN PATI SAGU YANG DISUBSTITUSI TEPUNG KACANG-KACANGAN - Agustia, Friska Citra; Subardjo, Yovita Puri; Sitasari, Almira (Jurnal Gizi dan Pangan, 2016)
The aims of the research were to determine the best formula and characteristics of free gluten with high protein sago starch noodles substituted with beans flour. A factorial random design was used for the experiment. Ratio of sago starch to red and green bean substitution were 100:0; 90:10; 80:20; 70:30. Variables analyzed were 1) chemical properties (water content, total fat, total protein, carbohydrate by difference and ash content) and 2) sensory properties. Hedonic test was conducted to determine the level of consumer acceptance of 15 semi-trained panelists. Data were analyzed by F-test and Duncan’s Multiple Range Test (DMRT). The best formula was sago starch noodle from sago starch 70% and red bean 30% with protein content 10.47% dry weight (dw); fat content 1.17% dw; water content 68.99% wet weight (ww); ash was 1.19% dw and carbohydrate by different was 18.18% dw. The hedonic test values were 2.44 (like slightly); color 2.77 (yellow-brown), texture 2.59 (chewy slightly) and flavour 2.50 (rather good).Keywords: green bean, red bean, sago starch noodle